Estimation of the Efficiency of the Operation of The Production Gas Well and Transfer It to the Stage of Capital Repair - R. A. Gasumov; E. R. Gasumov (Наука. Инновации. Технологии, 2022)
Introduction: The article discusses the reasons for shutting down production gas wells (PGW) and approaches to predicting the critical parameters in them to assess the need for transfer to the overhaul stage. The geological, technological and analytical stages of transferring wells to well workovers have been studied. Materials and methods of the research: The approaches to substantiating and assessing the impact of critical values of the bottom-hole formation zone parameters on the operation of the PGW for predicting the time of well shut-in are presented. The results of the study and their discussion: The main criteria are provided for assessing the efficiency of the PGW and the need to transfer the well to the workover program, which is a set of geological, technical, geological and production and production parameters that characterize the state of the bottom-hole formation zone, production wells and gas gathering network. The values of the threshold pressures for the Cenomanian productive formation were calculated, the values of the codes of the geological state of the wells by the formation pressure were assigned. The primary initial data for calculating the predicted flow rates of wells and their period of operation with a profitable level of flow rates of the PGW are presented. The conditions for selecting wells for successful workover have been determined, taking into account the value of the current reservoir pressure, which allows, at the required depression, to prevent the fallout of retrograde condensate in the bottom-hole formation zone. The main criteria for the selection of wells for workover, which allow obtaining potential super-, high- and medium well production rates, are stated. Conclusions: Well planning during the transition to workover is recommended to be carried out in three stages: geological, technological and analytical. A preliminary assessment of the feasibility of transferring wells to the overhaul stage makes it relatively easy to determine the sequence of well shutin, to identify from them that require immediate repair and (or) repair after a certain period of time. This assessment will allow assessing the effectiveness of repair work, optimizing their plans for carrying out, and reducing costs due to emergency failure of wells.